Community Attachment and Orchestration in Enhancing Tourism Performance for Economic Sustainability - Huddin, Muhammad Nurhaula (Applied Business and Administration Journal, 2025)
The Indonesian Ministry of Tourism actively promotes tourism villages with the objectives of empowering local communities, enhancing regional economies, and safeguarding cultural heritage. This paper underscores the significance of community attachment, emphasizing that residents not only derive benefits from tourism but also engage actively in its management, thereby contributing to the advancement of sustainable tourism practices. Furthermore, the concept of orchestration is examined as a strategic framework for effectively coordinating diverse stakeholders—comprising local communities, governmental entities, and businesses—toward the attainment of shared objectives. The orchestration actions, which encompass structuring, bundling, and leveraging, facilitate improved management of tourism villages by harmonizing interests, optimizing resource utilization, and enhancing planning and marketing initiatives. By employing the Resource-Based View (RBV), this study elucidates how the strategic leveraging of intangible assets, such as community attachment and local knowledge, can significantly influence tourism performance. It is anticipated that this paper will catalyze further conceptual and empirical investigations into this critical subject, offering valuable insights for tourism destination management and policymakers alike.